ONLINE GAMES AS THE MEDIA BEFORE HAVING EFL TEST (TOEFL EQUIVALENCE) FOR THE TWELFTH STUDENTS OF SMA NEGERI I JOMBANG 2018/2019 - Semani, Semani (JEELL (Journal of English Education, Linguistics and Literature) English Department of STKIP PGRI Jombang, 2019)
English is one of the compulsory subject for Senior High School. It is taught for two hours in a week. The students feel that the time is not enough for them because they must face national examination for it. SMA Negeri I Jombang has done additional course and joint with ITS language Center for Having EFL Test to measure the students’ ability in English. Before conducting the test, the teacher prepares them by using online game to make them familiar with English. After implementing it, the TOEFL Score/ EFL Test Score makes us satisfied. It is proved by there are more than 20 students of 36 students get more than 450.